Development of Student Worksheet based on Discovery Learning on Reproductive System Materials in Improving Higher Order Thinking Skills of Senior High School level-Madrasah Aliyah (MA) Students - Yuli Erpianna Harahap; Ummi Nur Afinni Dwi Jayanti (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2024)
Higher Order Thinking Skills (HOTS) are skills needed in the 21st century education world that must be mastered and developed. Therefore, innovative open materials are needed to help develop higher-order thinking abilities. This development research aims to produce a valid, practical, effective student worksheet based on discovery learning. The instruments used were needs analysis in the form of teacher interview guidelines and questionnaires for students, media and material expert validation sheets, and practicality sheets. Then the effectiveness sheet was a pretest post-test sheet. Based on the results of the data analysis, the validation of teaching materials obtained a score of 96.15%, the results of material validation obtained a score of 88%, the results of the teacher response questionnaire obtained a score of 100%, and the results of the student response questionnaire obtained a score of 98.66%. The effectiveness assessment resulted in a score percentage of N -Get 71.88% in the high category. Therefore, the student worksheet based on discovery learning are considered a feasible, practical, and effective learning tool, facilitating the development of high-level thinking skills. However, further research development can expand the material on biology learning that has yet to be covered in developing the student worksheet and expand the research scale